Counts of bacteria and pyocites of choledochal bile in controls and in patients with gallstones or common bile duct stones with or without acute cholangitis - Csendes, A; Mitru, N; Maluenda, F; Diaz, J C; Burdiles, P; Csendes, P; Pinones, E (Hepato-gastroenterology, 1996)
The number of colonies of bacteria and the number of pyocites present per ml of choledochal bile was studied. There were 42 controls, 100 patients with symptomatic gallstones, 42 patients with common duct stones without cholangitis and 24 patients with common duct stones and acute cholangitis. Control subjects had no bacteria present at gallbladder bile. Only 3% of patients with gallstones had more than 10(5) colonies per ml which increased to 36% in patients with common duct stones without cholangitis and to 84% among patients with acute cholangitis (p < 0.001). There were more polybacterial flora among patients with acute cholangitis and anaerobic bacteria were not seen in patients with gallstones. Patients with acute cholangitis had significantly more pyocites present at choledochal bile. There is a direct correlation between the number of colonies present per ml of choledochal bile and the severity of biliary tract disease. Patients with acute cholangitis had significantly more pyocites present at choledochal bile compared to gallstones or patients with CBD stones without cholangitis.